2020
DOI: 10.1016/j.ijsu.2020.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment in the response to the SARS-CoV-2 outbreak - A letter to the editor on “World Health Organization declares global emergency: A review of the 2019 novel coronavirus (COVID-19)” (Int J Surg 2020; 76:71–6)

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
(2 reference statements)
0
13
0
1
Order By: Relevance
“…The shortage of PPE due to COVID-19 pandemic is creating immense distress and heightened anxiety among healthcare workers [14] . In addition to general hygiene measures, it is suggested that different levels of protection should be adopted depending on the situation, and administrative measures are encouraged to minimize contact with infected patients [15] , [16] . In our study, more than half of the surveyed urologists (62.6%) stated that their center always or almost always had adequate PPE to cope with COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The shortage of PPE due to COVID-19 pandemic is creating immense distress and heightened anxiety among healthcare workers [14] . In addition to general hygiene measures, it is suggested that different levels of protection should be adopted depending on the situation, and administrative measures are encouraged to minimize contact with infected patients [15] , [16] . In our study, more than half of the surveyed urologists (62.6%) stated that their center always or almost always had adequate PPE to cope with COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Organizations like Public Health England (PHE), WHO, and Centers for Disease Control (CDC) have recommended the use of PPE for procedures on patients with suspected or confirmed COVID-19. [8,18,19] In this survey, we found that 57% of participants were using N95 masks while 66% were using surgical masks while operating on these patients. Complete PPE in the form of coverall was also being used by over 40% of the participants.…”
Section: Discussionmentioning
confidence: 79%
“…24 All members of the theatre team used PPE according to Trust protocols, including level 2-3 filtering face piece (FFP) masks, full face shield, double gloves and full body protection. High-risk staff were diverted to other lowerrisk activities, 25 and numbers within theatres were minimised, including the exclusion of observers and visitors. We also had two anaesthetists per theatre list to avoid PPE fatigue.…”
Section: Intra-operative Modificationsmentioning
confidence: 99%